2014
DOI: 10.1002/dneu.22196
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling participates in late phase differentiation of the retina, partly via upregulation of Hey2

Abstract: Bone morphogenetic protein (BMP) plays pivotal roles in early retinal development. However, its roles in the late phase of retinal development remain unclear. We found that BMP receptors and ligands were expressed in the postnatal mouse retina. Furthermore, immunostaining revealed that phosphorylated Smads were enriched in various cells types in the inner nuclear layer postnatally. However, phosphorylated Smads were not detected in photoreceptors, suggesting that BMP may play roles in retinal cells in the inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…S9A " type="url"/> ), suggesting that these transcription factors are not downstream of BMP signaling. Kuribayashi et al (2014 ) recently reported that BMP induces an expression of the basic helix-loop-helix (bHLH) transcription factor Hey2 during early retinal development (E17), and proposed that Hey2 might affect Müller glial development ( Kuribayashi et al, 2014 ). We did not observe a decrease in Hey2 expression when we inhibited BMP signaling in P6 retinal explants ( …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S9A " type="url"/> ), suggesting that these transcription factors are not downstream of BMP signaling. Kuribayashi et al (2014 ) recently reported that BMP induces an expression of the basic helix-loop-helix (bHLH) transcription factor Hey2 during early retinal development (E17), and proposed that Hey2 might affect Müller glial development ( Kuribayashi et al, 2014 ). We did not observe a decrease in Hey2 expression when we inhibited BMP signaling in P6 retinal explants ( …”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of Müller glia was assessed in this study by QR1 (Nqo1 – Mouse Genome Informatics) labeling (an extracellular matrix molecule specifically expressed in Müller glia); it is possible that the Müller glia were present but downregulated this differentiation marker, similar to GS or Cralbp in the present study. More recently, Kuribayashi et al found that overexpression of BMPR1a/b in E17 retinas led to an increase in the number of Müller glia, bipolar cells and amacrine cells, and a decrease in photoreceptors in vitro , whereas expression of dominant negative BMPR1a/b at E17 decreased the number of Müller glia and bipolar cells ( Kuribayashi et al, 2014 ). We did not observe any difference in the number of Müller glia, bipolar cells, amacrine cells and ganglion cells when BMP-Smad1/5/8 was inhibited in vivo at P6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distal domain and its overlaying surface ectoderm become thickened and invaginated, forming the inner layer of the optic cup and the lens vesicle, respectively. Inductive signals including fibroblast growth factors (FGFs) and bone morphogenetic proteins (BMPs) from the overlaying lens placode drive the inner layer of the optic cup towards becoming NR (Kuribayashi et al, 2014;Pandit et al, 2015;Pittack et al, 1997;Zhao et al, 2001). The proximal domain of the optic vesicle becomes the outer layer of the optic cup and develops into the RPE layer under the influence of the extraocular mesenchyme and the nearby overlying surface ectoderm (Fuhrmann et al, 2000;Muller et al, 2007).…”
Section: Formation Of the Optic Cupmentioning
confidence: 99%
“…We reported a slight but significant reduction in the number of bipolar cells in the INL of noggin 1-electroporated retinae with respect to GFP only retinae, but no significant differences were detected in the differentiation of other retinal subpopulations. Recently, two independent studies showed that a BMP wave is necessary to specify cells located in the INL of the mouse retina (Kuribayashi et al, 2014;Ueki et al, 2015), but no data are available for other vertebrates. Kuribayashi and collaborators (2014) showed that the overexpression of BMPs or BMP receptors increased the number of Müller glia and bipolar cells at the expense of rods, supporting the idea that BMPs play a pivotal role in the maturation of these two retinal cell types.…”
Section: (Ad) Wildtype Embryos At Stage 35 (A) and Stage 42 (D) (Bmentioning
confidence: 99%